Feeding Management Strategies among the Early Neolithic Pigs in the NE of the Iberian Peninsula. (30th June 2017) - Navarrete, V.; Colonese, A. C.; Tornero, C.; Antolín, F.; Von Tersch, M.; Eulàlia Subirà, M.; Comes, P.; Rosell‐Melé, A.; Saña, M.
Abstract: The socio‐economic relevance of domesticated animals during the Early Neolithic in the Iberian Peninsula is indisputable, yet we essentially know little about the way they were managed. Among domesticated animals, pig ( Sus domesticus ) was a common food source, and previous studies have shown the potential of stable isotopes for assessing variability in pig diet in relation to husbandry practices. Nevertheless, this approach has never been applied to the earliest pigs in the Iberian Peninsula. We analysed the carbon and nitrogen stable isotope composition of pig bone collagen from several Early Neolithic sites in the NE Iberian Peninsula. While pig δ 13 C values were similar across different populations, there were significant differences in δ 15 N values between sites. These are attributed to different pig husbandry systems, which may reflect distinct social and spatial organisation and interaction with environmental conditions during the Early Neolithic in this region. Copyright © 2017 John Wiley & Sons, Ltd.